Regular moderate exercise alleviates gastric oxidative damage in rats via the contribution of oxytocin receptors - (:unkn) unknown (WILEY, 2020)
Key points A moderate level of exercise has beneficial effects for the prevention of gastric ulcers. Although regular aerobic exercise was shown to elevate serum oxytocin levels and exogenously administered oxytocin exerts an anti-ulcer activity, the role of endogenous oxytocin in the gastroprotective effects of exercise has not yet been elucidated. We showed that increased anxiety and oxidative gastric damage induced by gastric ulcers were reversed in pre-exercised rats, while reduced hypothalamic oxytocin expression and decreased myenteric oxytocin receptor expression due to gastric ulcers were abolished by exercise. We also reported that the blockade of oxytocin receptors exaggerated gastric damage in exercised rats with ulcers. Our data establish that endogenous oxytocin is the key mediator in the beneficial effects of regular physical activity in alleviating gastric injury. Exercise increases serum oxytocin levels and exogenous oxytocin exerts an anti-ulcer activity; but the role of oxytocin in the protective effects of exercise against gastric ulcers has not yet been evaluated. This study was designed to investigate the impact of regular swimming exercise on oxidative gastric injury, and the role of oxytocin receptor activity in the anxiolytic and anti-inflammatory actions of exercise. Adult Wistar albino rats of both sexes performed swimming exercise (30 min/day, 5 days) or stayed sedentary. At the end of the 6-week exercise/sedentary protocol, rats were injected intraperitoneally with atosiban (0.1 mg/kg/day) or saline for 4 days. On the 5th day, under anaesthesia, acetic acid (ulcer) or saline (sham) was applied onto the gastric serosa and the treatments were continued. On the 9th day, anxiety levels were determined; gastric blood flow was measured, and blood, gastric and brain tissues were obtained. Induction of ulcers in sedentary rats increased anxiety and serum corticosterone levels; but reduced gastric blood flow and resulted in apoptosis and oxidative gastric damage with increased cytokine expressions. However, when ulcers were induced in pre-exercised rats, behavioural and biochemical alterations due to gastric damage were reversed. The inhibition of oxytocin receptors by atosiban exaggerated pro-inflammatory cytokine expressions and gastric lipid peroxidation in the stomachs of exercised rats with ulcers. When rats had regularly exercised prior to ulcer induction, reductions in the immunolabelling of hypothalamic oxytocin and myenteric oxytocin receptors were abolished, suggesting that exercise-induced alleviation of gastric injury may involve the reversal of down-regulated oxytocinergic activity.
Keywords: atosiban; exercise; gastric ulcer; inflammation; oxytocin; PHYSICAL-ACTIVITY REDUCE; PITUITARY-ADRENAL AXIS; PEPTIC-ULCER; NITRIC-OXIDE; DUODENAL-ULCERS; ORGAN DAMAGE; STRESS; VASOPRESSIN; BRAIN; INFLAMMATION